Análisis de Estabilidad Probabilístico del Talud de la Cantera Espinal – Juliaca - Valeriano Nina, Fredy Alonso (2018)
This study was carried out in the Espinal highway of Juliaca city in the state of Puno, which consists in to determinate the safety values that controls the stability or instability of a rocky slope; safety factor (FS) or shear strength reduction (SRF) and failure probability (PF). Due to this, general methods of rock slope stability were used; cinematic analysis and numerical methods. Probabilistic analyses were conducted by the method of points’ estimation for more reliability in the results of numerical methods. Having in the cinematic analysis results a probability of glide plane by direct toppling of 44.41%, the values of average safety obtained by the probabilistic analysis with numerical methods in SFR are; for static conditions FS or SRF 2.27 and PF 0.0% and for pseudostatical conditions a FS or SRF 1.21 and PF 2.98%. Due to this, we concluded that the slope is stable in static and pseudostatic conditions, considering the results of cinematic analysis, were observed tension cracks on the top of the slope which failed by direct toppling depending of the intensity of trigger factors.